THE DEVELOPMENT VOCATIONAL WELL-BEING TAXONOMY FOR SOCIAL AND ECONOMIC SUSTAINABILITY OF THE NATION: A REVIEW - Lambin, Regina; Mustapha, Ramlee; Long, Norhazizi Lebai; Sharif, Mohd Penislin Md (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to develop Vocational Well-Being Taxonomy for the social and economic sustainability of the nation. Well-being is the value of an individual's happiness and contentment, and it also refers to the physical, emotional, spiritual, and cultural comforts that can be achieved when the needs are met. It is closely related to psychological capacity and human capital skills. The concept of well-being is closely related to human capital that can be translated into individual skills, as highlighted in TVET. TVET agenda is also highlighted as one of the strategies in achieving Shared Prosperity Vision 2030. The purpose of Shared Prosperity Vision 2030 is for Malaysia to make life quality as a developed nation focused on the well-being of the people through various innovation strategies and transformation. However, Malaysia still critically lags in terms of the number of skilled workers, accounting for only 20% as compared to OECD countries such as Germany (60%), Singapore (51%), and Finland (43%). The main problem with the education system in Malaysia is that it focuses too much on the academic stream so that the vocational stream is considered second class. As the rate of unemployment among the academic stream begins to rise, there is awareness to enhance students’ participation in the vocational stream to ensure the well-being of the people in terms of getting a job. In academic education, Bloom's taxonomy was created to classify educational goals, objectives, and outcomes. But Bloom's Taxonomy does not meet the criteria for assessing "well-being" through vocational skills in order to get a job in highly-skilled fields. The well-being of the people through full-employment may not be achieved without the strategy of increasing skilled workers through TVET. As such, it is critical to determine the important domains for vocational well-being that could be developed as a taxonomy for the social and economic sustainability of the nation. This initial study will employ a thorough review of relevant literature and theories.